“What ails victimology?” Revisited: Assessing the growth and development of victimology as an academic discipline - Beichner-Thomas Dawn; James Chadley; Piason Bothwell (Temida, 2025)
More than fifteen years have passed since Jaishankar (2008) published the editorial, “What ails Victimology?” in the International Journal of Criminal Justice Sciences, in which he outlined his perceptions of why victimology has struggled to be recognized as a distinct academic discipline. We revisit the five areas outlined in Jaishankar’s (2008) argument and explore the growth of the victimology discipline over the past decade and a half. The exploration considers theoretical development, content of published scholarly journal articles, courses, curricular programs, published academic books, and peer-reviewed journals, from 2008 to 2023. It is concluded that most of the “symptomatic failings” that Jaishankar (2008: 2) outlined as hampering the growth of victimology seem to be resolved, including concerns about acceptance of the discipline in the larger international community. However, there is room for new theoretical developments in victimology and more graduate-level degree programs.